Reclaiming Indigenous Identity through Animal Advocacy in Art: Adrian Stimson and Dana Claxton - Kozak, Luba Stephania (Humanimalia, 2019)
The buffalo is an animal of utmost importance in many Plains Indigenous tribes that holds great historical and spiritual significance. This paper analyzes the representation of the buffalo in the artworks of First Nations artists Adrian Stimson and Dana Claxton, with excerpts from an exclusive interview with Stimson. Through an observation of cross-species encounters in the work of Stimson and Claxton, this paper demonstrates how art can be used as a medium for animal advocacy by situating the non-human within a cultural context, which contributes to the concept of human identity and illustrates alternative Niitsapi perspectives. Posthumanist thought, as well as Indigenous perspectives on human and non-human relations that challenge the decolonizing of posthumanist ideals, will frame the arguments posed in this paper to explore issues of colonial trauma, Indigenous identity, and animal rights.